Le testament de Nunó Sanç, seigneur de Roussillon et de Cerdagne (17 décembre 1241) - Rodrigue Treton; Robert Vinas (E-Spania)
The character of Nunó Sanç couldn't be left out of an history review devoted to the bonds which have united the Roussillon province with Majorca. The authors of this article have decided on publishing in its whole, in latin and in a French translation, well-supplied with notes, the will of the Lord of Roussillon whose ancestry they also have restored. That text, in which Nunó, on the eve of his own death, makes his peace with God and with men, will reinforce the importance of a character who is deliberately in keeping with a mediterranean angle.